2015
DOI: 10.1007/s10853-015-9349-6
|View full text |Cite
|
Sign up to set email alerts
|

Functional composites with core–shell fillers: I. Particle synthesis and thermal conductivity measurements

Abstract: Filled epoxy composites are broadly used in electronic and power devices as an electrical insulation. It is of importance to achieve efficient heat dissipation in such devices due to fact that thermal properties have a strong influence on their proper operation. For this reason, the modification of standard filler materials, such as silica or alumina, can give a promising solution. In this work, a novel core-shell material has been proposed and manufactured by means of a carbothermal reduction and nitridation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
32
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 40 publications
(41 reference statements)
1
32
0
Order By: Relevance
“…Several examples of different core–shell particles have been previously described . Recently, the authors have demonstrated a successful approach with a fully ceramic core–shell fillers synthesis by means of carbothermal reduction and nitridation process which were incorporated into epoxy matrix in order to create electrical insulation with enhanced thermal conductivity …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several examples of different core–shell particles have been previously described . Recently, the authors have demonstrated a successful approach with a fully ceramic core–shell fillers synthesis by means of carbothermal reduction and nitridation process which were incorporated into epoxy matrix in order to create electrical insulation with enhanced thermal conductivity …”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22][23] Recently, the authors have demonstrated a successful approach with a fully ceramic core-shell fillers synthesis by means of carbothermal reduction and nitridation process which were incorporated into epoxy matrix in order to create electrical insulation with enhanced thermal conductivity. [24] In this work, a polymer derived ceramics (PDCs) technique has been applied in order to produce a filler whose core is composed of silica flour, covered by boron nitride (BN) and silicon nitride (Si 3 N 4 ) shell. The PDCs are a known synthesis method for creating advanced ceramic materials.…”
Section: Introductionmentioning
confidence: 99%
“…However, pure polymers do not exhibit the required physical properties such as high thermal or electrical conductivity and they are usually classified as thermal and electrical insulators. So far, many studies have been carried out in order to improve these properties by incorporation of conductive particles, such as metal or ceramic particles [2,3] into polymer [4,5] matrix. Recently, much attention of leading research centers dealing with heat transport in thermally conductive composites has been focused on various fillers and methods of arrangement of their particles that could improve the thermal conductivity of polymeric formulae.…”
Section: Introductionmentioning
confidence: 99%
“…In order to improve mechanical properties, whilst also ensuring enhanced thermal conductivity, various fillers may be incorporated into the polymer matrix. Examples of filler that may be used include silica, which with a thermal conductivity of up to 10 W/mK [3][4][5][6] is the most popular filler material, or boron nitride which represents a more sophisticated (with a thermal conductivity of up to 600 W/ mK) but costly solution [7,8]. One can find attempts to add carbon nanotubes or graphene [9,10], however such fillers are electrically conductive and cannot be applied for composites used as electrical insulation.…”
Section: Introductionmentioning
confidence: 99%
“…Acoustic mismatch of two mixed materials results in additional phonons scattering at the boundaries, as they are transported through the interface between the filler and the matrix. As a consequence, interfacial thermal resistance can occur [4,7]. This problem may be solved through enhanced coupling between a filler and a matrix [16].…”
Section: Introductionmentioning
confidence: 99%